Diversity within diversity management country-based perspectives - Georgiadou, Andri; Gonzalez-Perez, Maria Alejandra; Olivas-Lujan, Miguel R. (Bingley, U.K. Emerald Publishing Limited, 2019)
Nowadays, managing and promoting diversity is of paramount importance to the future of sustainability and the political and business agenda. Despite a tremendous growth in diversity management scholarship in recent years, a strong tendency has emerged whereby existing theories focus on a single level of analysis, using a limited range of mostly Western research settings, and on a narrow range of diversity types. Diversity research has insofar focused on prioritizing visible forms of diversity, such as gender or disability, with less emphasis placed on diversity in culture and values internationally. This edited book provides new practical and strategic insights for practitioners, managers, students and policy makers; it delves into the strategic nature of policy intervention with thought-provoking contributions written by experts from around the world. Contributors aim to provide critical reflection of current debate areas on workplace equality and diversity in under-researched countries to inform and support evidence-based decision making for a wide variety of academic and practice-oriented stakeholders
Prelims -- Diversity within diversity management: where we are, where we should go, and how we are getting there -- Managing diversity in Nigeria: competing logics of workplace diversity -- Diversity management: the case of the United Arab Emirates -- Diversity management in sustainability reports: a case study from Turkey -- Managing diversity in Australia: a viable career option, social change agents, or corporate stepping stone? -- Diversity in the Czech Republic -- Diversity management in Slovenia -- Managing diversity in South African higher education institutions -- Gastronomy as a national identity element: the Peruvian case -- Gender in Venezuelan board of directors and c-level positions: current balance of gender diversity for twenty-first century socialism -- Diversity management in Poland -- A changing country: diversity management in Greece -- Workplace diversity and inclusion policies: insights from a foreign firm in the Nigeria banking sector -- Managing diversity in Trinidad and Tobago -- Shifting landscapes of diversity in India: new meaning or a contextual shift? -- Diversity management in Taiwan: the case of the semiconductor industry -- Indigenous entrepreneurship, society, and the dimensions of diversity: an overview of the Canadian national context -- Diversity management and inclusion in Afghanistan -- Index
Includes index
Keywords: Cultural pluralism; Personnel & human resources management / bicssc; Business & Economics / Human Resources & Personnel Management / bisacsh; Diversity in the workplace